Proceso de atención de enfermería en gestante de 37,5 semanas con Covid 19 - Tenelema Valencia, Jeniffer Katherine (2021)
The COVID 19 known as SARS-COV-2 that was identified in each country around the world influencing the pandemic that still remains at a high level of incidence in the mortality rate, the main characteristic of this virus is to affect the respiratory system causing complications in the different organs, this contagion began in the city of Wuhan at the end of 2019 and the beginning of 2020 until today, being its condition in vulnerable people such as older adults.In the following case study we will present the clinical history of a pregnant patient with 37.5 weeks of gestation with a symptomatological picture of cough, fever, dyspnea with a saturation of 93%. The tests essential for the diagnosis of COVID 19 were performed. During this clinical study through the nursing assessment by functional patterns, Nursing Diagnosis, Planning of the results and the intervention of activities, the care plans that were directed were elaborated In the main problems that were discovered through the interview, improving the patient's health status together with their medical treatment, complications such as premature birth were also established. Education was provided to the family and their patient about the care that they should follow at home, plus isolation. A surgical intervention for cesarean section was scheduled on June 30, 2020.